Integration of Emotional and Spiritual Intelligence in Teacher Education Curriculum: a Holistic Approach - Behera, Narayan Prasad; Mohanty, Sukanta Kumar (JOURNAL OF INDIAN EDUCATION, 2013)
This article analyses the existing teacher education curriculum critically and counsels inclusion of emotional and spiritual intelligence as a core necessity to meet the educational challenges. Some suggestions are delineated for inclusion of emotional intelligence (E.I) and spiritual intelligence (S.I) in our teacher education programme.